Pengaruh Destination Image Terhadap Minat Merekomendasikan Daya Tarik Wisata Pantai Sasak Dengan Destination Personality Sebagai Variabel Moderasi (Jurnal Manajemen Pariwisata dan Perhotelan, 2025)
This research aims to analyze the influence of Destination Image on Interest in Recommending Sasak Beach Tourist Attractions with Destination Personality as a Moderating Variable. This type of research is quantitative descriptive with a sampling technique using purposive sampling and a sample size of 170 respondents based on the hair formula. The instrument in this study used a questionnaire arranged according to a Likert scale and data was collected by distributing the questionnaire that had been prepared and then given to respondents whose validity and reliability had first been tested. Based on the research that has been carried out, the following results were obtained: Destination Image (X) is in the sufficient category with a percentage of (3.33%). Interest in Recommending (Y) is in the sufficient category with a percentage of (3.32%). Destination Personality (Z) is in the sufficient category with a percentage of (3.34%). There is a positive and significant influence between the Destination image (X) variable on the Interest in Recommendation (Y) variable with a t-statistic value of 6.378 which is greater than the t-table value of 1.96 and a p-value of 0.00 which is smaller than 0.05. There is no positive and significant influence between the Destination Personality (Z) variable which moderates the relationship between Destination Image (X) and Interest in Recommending (Y) with a t-statistics value of 0.885 which is smaller than 1.96 with a p value of 0.885. 0.377 is greater than 0.05, and the original ample value is 0.037.